Green Economy: In Pursuance of Sustainable Development - Adhikary, Dileep K (Administration and Management Review, 2012)
We have reached a time where the understanding of development should not be pursued in isolation but should best be interfaced with nature for an improved and sustained quality of life. The pursuit of green economy requires a considerable change in our approach to development wherein the greening of the sectors needs to be planned at the very outset of the process. This paper, has conceptualized, and discusses strategic thrust, sectoral integration, management dynamism and institutional and policy regime as a basic embodiment in a green economic framework. It may involve mobilisation of additional resources but is worth an investment for all smiles in near future. Green Economy Framework is a critical stepping in leading to sustainable development which is indeed an ability to transform from one phase of the timeline to the other phase. Administrative and Management Review Vol. 24, No. 2, August 2012, Page 77-90